Peoples' tribunals and international law - Byrnes,Andrew,Ed.; Byrnes, Andrew; Simm, Gabrielle (UK, Cambridge, 2018)
"Peoples' Tribunals and International Law is the first book to analyse how civil society tribunals implement and develop international law. With contributions covering tribunals in Europe, Latin America and Asia, this edited collection provides cross-disciplinary academic and activist perspectives and unique insights into the phenomenon of peoples' tribunals. Written by academics in law, anthropology and international relations, it also incorporates the reflections of civil society activists and advocates on peoples' tribunals. The collection includes chapters ranging from the Permanent Peoples' Tribunal, successor to the Bertrand Russell Tribunal established to question the legality of the Vietnam War, to recent tribunals addressing atrocities in Soeharto's Indonesia and violations against migrants in Europe. Peoples' Tribunals and International Law offers the first sustained analysis of the different approaches to international law in tribunal proceedings. It will interest scholars of law, criminology, human rights, politics, sociology, anthropology and international relations"--
Machine generated contents note: Introduction Andrew Byrnes and Gabrielle Simm; Part I. Introduction: History of peoples' rribunals: 1. International peoples' tribunals: their nature, practice and significance Andrew Byrnes and Gabrielle Simm; 2. The history of the Permanent Peoples' Tribunal Gianni Tognoni; Part II. The Politics of Bearing Witness and Listening: 3. Peoples' tribunals, women's courts and international sexual violence crimes Gabrielle Simm; 4. The Tokyo Women's Tribunal: transboundary activists and the use of law's power Tina Dolgopol; 5. The International People's Tribunal on 1965 crimes against humanity in Indonesia: an anthropological perspective Saskia E. Wieringa; 6. The participation of peoples in the development of international law: the laboratory of the Permanent Peoples' Tribunal Simona Fraudatario and Gianni Tognoni; Part III. Legal Pluralism and Popular International Law: 7. Accusing 'Europe': articulations of migrant justice and a popular international law Sara Dehm; 8. The Permanent Peoples' Tribunal and indigenous peoples' struggle in Mexico: between coloniality and epistemic justice Rosalba Icaza Garza; 9. Evaluating the Biak Massacre Citizens' Tribunal and the disputed Indonesian region of West Papua Nicola Edwards; 10. Assessing the contribution of the Latin American Water Tribunal to transnational environmental law Belen Olmos Giupponi; Part IV. The Future of International Peoples' Tribunals: 11. Reflections on the past and future of international peoples' tribunals Andrew Byrnes and Gabrielle Simm.
Includes papers presented at the expert seminar of people's tribunals and international law on 27-28 September 2013 in Rome at the Permanent Peoples' Tribunal under the sponsorship of the Australian Human Rights Centre of the University of New South Wales, Sydney, Australia.
Includes bibliographical references and index.
Keywords: International law -- Congresses; International courts -- Congresses; International criminal law -- Congresses; Human rights and international law -- Congresses